Answer:
x = 2, y = 1
Step-by-step explanation:
x + 4y = 6 and y = 3 - x have to be rearranged: x + 4y = 6 and x + y = 3
You subtract the equations to eliminate one of the variables (x) so that the other can be found
Answer:
44
Step-by-step explanation:
she set aside $44 for vacation
pls brainliest btw
(3x + 1/2 ) + ( 7x - 4 1/2 )
3x+7x + 1/2 - 4 1/2
10x -4
D) you just multiply the numerator and denominator by 6 to get an equivalent fraction
Answer:
C≈402.12in
Step-by-step explanation:
The circumference of a circle is equal to pi times the diameter. The diameter is two times the radius, so the equation for the circumference of a circle using the radius is two times pi times the radius